A new serotype 14 variant of the pneumococcal Spain9V-3 international clone detected in the central region of Argentina - Albarracín Orio, Andrea Georgina (2008)
The penicillin-resistant Spain9V-3 clone of Streptococcus pneumoniae is widespread and presents different serotype variants originating from recombination of the capsular genes. In this work, the genetic relatedness of 29 invasive pneumococci isolated from the central region of Argentina (Cordoba, Buenos Aires, Santa Fe and La Pampa provinces) was assessed by multilocus sequence typing (MLST). All of the penicillin-non-susceptible isolates studied (21/29) belonged to a serotype 14 variant of the Spain 9V-3 clone. This clone was predominant, suggesting that it was responsible for the penicillin resistance spread in this region. Interestingly, this serotype 14 variant (named Cordoba S14V) could be differentiated from the European one by its pbp1a gene, suggesting a different recombinational replacement of the capsular genes. The putative recombination sites were analysed, resulting in the proximal crossover point being clearly localized in the spr0309 gene, with the distal site restricted to the recU gene, confirming a different recombination event. Analysis of the dexB, cpsB, aliA and pbp1a genes from these strains showed a high similarity with the corresponding genes of the Spain14-5 clone, suggesting that the capsular genes were provided by this international clone. Analysis of the genetic polymorphisms of the pbp1a (nt 1473-1922) and spr0309 (nt 1-790) genes is proposed as an epidemiological tool to help recognize the Cordoba S14V of the Spain9V-3 clone. On the other hand, BOX-repeat-based PCR and MLST analyses of serotype 14 strains revealed a divergent epidemiology of the Cordoba S14V, suggesting a non-recent dissemination in the paediatric population. It is suggested that this molecular epidemiology work will be a reference for monitoring the evolution of S14Vs of Spain9V-3, the emergence of new clones and the impact of pneumococcal vaccination programmes in Argentina.